How companies could adapt disclosures in annual / sustainability reports as proxy data for BNM taxonomy reporting to obtain green financing - Palaniappan, Thenappan (2022)
Almost every country on the planet agreed in 2015 to keep global average temperature rises far below 2 degrees Celsius, ideally to 1.5 degrees Celsius, to prevent the worst effects of climate change. To reach this climate ambition, the Paris Agreement will require US$ 1.5 trillion in green investment per year until 2030. Human activity, however, has already heated the earth by around 1.1°C, according to the Intergovernmental Panel on Climate Change (IPCC) climate study released in August 2021. Worse still, based on current emission trends, 1.5°C of warming will be reached by 2040 or earlier if nothing is done. Based on the current cumulative Nationally Determined Contributions (NDCs), it’s evident that adaptation measures and technologies at scale to decarbonize are still not available. Current environmental-related disclosures by top companies in Malaysia are still elementary. Sustainability reports are increasingly being used for legitimizing and are highly skewed for public relations (PR) purposes. Furthermore, present disclosures are not clear or comparable across industries, as it is practically hard to compare organizations based on ESG performance due to annual changes in methodology, measurements, and standards. There is also the issue of adaptability with current disclosures through annual reports having little to no effect in obtaining green financing from financial institutions or in compliance with Bank Negara Malaysia’s Climate Change and Principle-based Taxonomy. According to the KPMG 2021 CEO Outlook study, 70% of CEOs in Asia-Pacific stated businesses are facing greater demand from stakeholders for more reporting and transparency on ESG concerns, with institutional investors (57%) and regulators (31 percent ) being the primary sources of pressure. Given this, this paper seeks to develop an all-inclusive, practical, and extensive environmental framework that public listed companies in Malaysia could adopt as a standard for their annual sustainability report, which allows them to access green financing easily and comply with the requirements of BNM’s CCPT. Adopting a multi-stakeholder approach while incorporating numerous international standards such as GRI and TCFD, the framework was tested and improved with inputs and feedback from various private sector and non-governmental experts on sustainability. Future work involves, adjusting the framework and customizing the criteria in-line with the International Sustainability Standards Board (IFRS-ISSB)’s requirements that will be released in the second half of 2022 specific to carbon-intensive sectors such as oil & gas, utilities, construction, logistics, and transportation.